PERAN GURU SD SEBAGAI EDUPRENEUR: MOTIVASI, STRATEGI, TANTANGAN MENDIRIKAN LEMBAGA BIMBINGAN BELAJAR - Diana Arifyana; Nawal Ula Sakinah; Isnaeni Mutiara; Aulia Isdiyana (CV. Denasya Smart Publisher, 2025)
This study examines the establishment and management of Griya Bimbel Kwayangan as a concrete example of edupreneurship in non-formal education. This tutoring center was founded in 2010, initially as a simple door-to-door private tutoring service for elementary school students. Over time, this tutoring center has grown into a popular home-based tutoring institution, even without formal promotion, but rather through word of mouth. The purpose of this study is to determine the background of the establishment of the tutoring center, the management strategies applied, the challenges faced, and the impact on both students and managers. The results of the study show that the success of the tutoring center is supported by factors such as family support, flexibility in learning methods according to student needs, the use of digital technology through interactive media such as online quizzes, and intensive communication with parents who also monitor their children's learning progress. Positive impacts can be seen in the improvement of students' academic achievement, the formation of better learning motivation, and a close emotional relationship between teachers and students. Meanwhile, for managers, the existence of this tutoring center is a means to hone academic skills and develop an entrepreneurial spirit in the field of education. However, challenges remain, particularly limited funds, inadequate learning facilities, and a shortage of teaching staff. In conclusion, Griya Bimbel Kwayangan shows that edupreneurship can grow from simple initiatives and strong commitment, capable of making a real contribution to improving the quality of student learning. This study also implies that the development of home-based tutoring institutions can be an alternative solution for community education if supported by innovation, collaboration, and planned sustainability.